2021
DOI: 10.31234/osf.io/gyhd9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 on anxiety and wellbeing for families of individuals with Special Education Needs and Disabilities in the UK

Abstract: COVID-19 has affected people across the world. However, it has been suggested that individuals with Special Education Needs and Disabilities (SEND) and their families might have been particularly impacted by the first national lockdown in the UK. In contrast to previous studies, the current study examined wellbeing and anxiety at different time points and included a control group matched for family situation. Parents of 402 individuals with SEND reported on their own anxiety and wellbeing as well as that of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Our survey, launched in the first months of the pandemic, allowed us to study ER strategy use and the link to anxiety in neurodevelopmental disorders, namely, in individuals with WS, autistic people with and without ID, and individuals with ID-NOS. Individuals with neurodevelopmental disorders have been disproportionally affected by the COVID-19 pandemic with increased levels of anxiety and other mental health outcomes ( 46 , 47 , 65 , 66 ). While our current analysis does not allow a comparison with typically developing individuals, we observed that autistic people (with and without ID) had elevated anxiety levels compared to individuals with ID-NOS, in line with previous studies reporting prevalence rates of 42–79% in autistic people ( 67 ) while prevalence rates seem lower in individuals with ID [3–22%, ( 68 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey, launched in the first months of the pandemic, allowed us to study ER strategy use and the link to anxiety in neurodevelopmental disorders, namely, in individuals with WS, autistic people with and without ID, and individuals with ID-NOS. Individuals with neurodevelopmental disorders have been disproportionally affected by the COVID-19 pandemic with increased levels of anxiety and other mental health outcomes ( 46 , 47 , 65 , 66 ). While our current analysis does not allow a comparison with typically developing individuals, we observed that autistic people (with and without ID) had elevated anxiety levels compared to individuals with ID-NOS, in line with previous studies reporting prevalence rates of 42–79% in autistic people ( 67 ) while prevalence rates seem lower in individuals with ID [3–22%, ( 68 )].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that maladaptive strategy use such as catastrophizing, rumination, or excessive health-related information seeking was correlated with increased perceived distress, negative emotions, depression, and anxiety, while adaptive strategies (including positive refocusing and acceptance) have acted as a buffer to alleviate emotional distress and negative emotions during COVID-19 in the general population (38)(39)(40)(41)(42)(43)(44). It has even been suggested that individuals with neurodevelopmental disorders and their families have been disproportionally impacted (45)(46)(47). For example, in a study including individuals with attention deficit and hyperactivity disorder, poorer pre-COVID-19 ER abilities were linked to increased mental health symptoms (48).…”
Section: Introductionmentioning
confidence: 99%
“…An international network of collaborators translated and disseminated the questionnaire in 16 languages, eventually reaching more than 10,000 families in 78 countries around the world. The questionnaire (original English version available in Supplementary Materials) and database have been used for other papers that have been published (Su et al, 2021;Furar et al, 2022;Sideropoulos et al, 2022aSideropoulos et al, , 2022b. One parent of each family completed the anonymous survey which contained a total of 299 questions.…”
Section: Methodsmentioning
confidence: 99%
“…A selection from the entire list of concerns was made both to test our hypotheses as well as to investigate other potential operable, as opposed to abstract, environmental barriers encountered by these families over time. Therefore, all health-related concerns (e.g., about illness in general, about COVID-19, about the child's health) were excluded from these analyses because they were not operable environmental barriers that could reveal environmental facilitators capable of improving activity and participation in daily life (for an overview of health-related concerns in the UK, see Sideropoulos et al, 2022a). In addition, the concern about "financial and economic problems" was removed from the model for individuals with NDCs because their average age was only 12.…”
Section: Multilevel Analysis Proceduresmentioning
confidence: 99%